Analytical Analysis of Extreme Position Mechanisms for Conveyor Lifting Segments Using Kinematic Systems - Radite Raharja; Julius Pandu Winata; Rasyid Yudhistira; Lobes Herdiman (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
The process of moving an item in the industrial world has an influence on productivity produced by the company. The company's productivity can be supported by using a conveyor when the transfer process takes place. This study aims to determine the extreme position of the conveyor lift segment mechanism using the kinematic system. The method used is an analytical analysis method with a kinematic system using SAM 6.0 software. The stages of the research process are measuring conveyor segments, drawing kinematic diagrams, depicting movement mechanisms, calculating degrees of freedom (DoF), calculating geometry, and ending the stroke link follower measurements. The results of the study resulted in a degree of freedom that is 1 which shows the movement of the conveyor freedom only 1 direction, and the calculation result of follower link stroke is 22.6o which shows the maximum range that can be done from the movement of the conveyor lifting segment.